Multi‐dimensional biodiversity hotspots and the future of taxonomic, ecological and phylogenetic diversity: A case study of North American rodents. Issue 3 (10th January 2020) - Smiley, Tara M.; Title, Pascal O.; Zelditch, Miriam L.; Terry, Rebecca C.
Abstract: Aim: We investigate geographic patterns across taxonomic, ecological and phylogenetic diversity to test for spatial (in)congruency and identify aggregate diversity hotspots in relationship to present land use and future climate. Simulating extinctions of imperilled species, we demonstrate where losses across diversity dimensions and geography are predicted. Location: North America. Time period: Present day, future. Major taxa studied: Rodentia. Methods: Using geographic range maps for rodent species, we quantified spatial patterns for 11 dimensions of diversity: taxonomic (species, range weighted), ecological (body size, diet and habitat), phylogenetic (mean, variance, and nearest‐neighbour patristic distances, phylogenetic distance and genus‐to‐species ratio) and phyloendemism. We tested for correlations across dimensions and used spatial residual analyses to illustrate regions of pronounced diversity. We aggregated diversity hotspots in relationship to predictions of land‐use and climate change and recalculated metrics following extinctions of IUCN‐listed imperilled species. Results: Topographically complex western North America hosts high diversity across multiple dimensions: phyloendemism and ecological diversity exceed predictions based on taxonomic richness, and phylogenetic variance patterns indicate steep gradients in phylogenetic turnover. An aggregate diversity hotspot emerges in the west, whereas spatial incongruence exists across diversity dimensions at the continental scale. Notably, phylogenetic metrics are uncorrelated with ecological diversity. Diversity hotspots overlap with land‐use and climate change, and extinctions predicted by IUCN status are unevenly distributed across space, phylogeny or ecological groups. Main conclusions: Comparison of taxonomic, ecological and phylogenetic diversity patterns for North American rodents clearly shows the multifaceted nature of biodiversity. Testing for geographic patterns and (in)congruency across dimensions of diversity facilitates investigation into underlying ecological and evolutionary processes. The geographic scope of this analysis suggests that several explicit regional challenges face North American rodent fauna in the future. Simultaneous consideration of multi‐dimensional biodiversity allows us to assess what critical functions or evolutionary history we might lose with future extinctions and maximize the potential of our conservation efforts.